ANALISA KOMPETENSI KARYAWAN SEBAGAI VARIABEL MODERASI ANTARA KNOWLEDGE SHARING DAN EFEKTIVITAS PELATIHAN TERHADAP KINERJA KARYAWAN - Lestari, Irena Sri; Rahmawati, Rini (JWM (JURNAL WAWASAN MANAJEMEN), 2023)
The aim of this study is to discover and evaluate the impacts of knowledge transfer and training efficacy on employee performance, with employee competency serving as a moderator. 40 employees from the Bank Kalsel Amuntai Branch took part in this survey as responders. The analytical application used is called SmartPLS. The study's conclusions show that training effectiveness and information sharing both have positive and substantial influence on worker performance. The impacts of information exchange and training efficacy on performance are also moderated by employee competency